Chinese aid and health at the country and local level - Cruzatti, John; Dreher, Axel; Matzat, Johannes (World development, 2023)
We investigate whether and to what extent Chinese development finance affects infant mortality, combining 92 demographic and health surveys (DHS) for a maximum of 53 countries and almost 55,000 sub-national locations over the 2002-2014 period. Our results show that Chinese aid decreases infant mortality at the country level. Relative to the country average, aid however increases infant mortality at sub-national scales. In several tests, we show that this stark contrast likely results from aid being fungible within recipient countries.
Gesehen am 26.05.2023
Keywords: China; Entwicklungsländer